Autophagy–NAD+ axis: emerging insights into neuronal homeostasis and neurodegenerative diseases - Kocak, Gamze; Dimas, Mylla M.; Silva, Luiz F. S. E.; Silva-Amaral, Danyelle; Sun, Congxin; Cruddas, Sophie; Barrett, Timothy; Martins-de-Souza, Daniel; Cunha-Neto, Edecio; Brocardo, Patricia S.; Kataura, Tetsushi; Korolchuk, Viktor I.; et al. (Frontiers in Molecular Biosciences, 2025)
Autophagy is an evolutionarily conserved catabolic process that plays a central role in maintaining cellular homeostasis by degrading and recycling damaged or surplus proteins, organelles, and other cellular macromolecules and components. A growing body of evidence highlights a bidirectional relationship between autophagy and nicotinamide adenine dinucleotide (NAD+), a vital metabolic cofactor involved in numerous cellular processes, including energy metabolism, genomic maintenance, stress resistance, and cell survival. Autophagy supports NAD+ homeostasis by recycling metabolic precursors, while NAD+-dependent enzymes such as sirtuins and PARPs regulate autophagy initiation and lysosomal function. Disruption of this autophagy–NAD+ axis has emerged as a common feature in several neurodegenerative diseases, where impaired cellular clearance and metabolic dysfunction contribute to neuronal vulnerability. In this review, we summarize the advances of the molecular links between autophagy and NAD+ metabolism, with a particular focus on their roles in mitochondrial quality control, bioenergetic regulation, and cellular resilience. We also discuss the therapeutic potential of targeting the autophagy–NAD+ axis to promote neuroprotection in neurodegenerative disease.